1998
DOI: 10.1161/01.atv.18.6.999
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Stimulates Apolipoprotein A-I– but Not A-II–Containing Particle Synthesis and Secretion by Stimulating mRNA Transcription Rate in Hep G2 Cells

Abstract: Abstract-Estrogen therapy increases plasma HDL levels, which may reduce cardiovascular risk in postmenopausal women. The mechanism of action of estrogen in influencing various steps in hepatic HDL and apolipoprotein (apo) A-I synthesis and secretion are not fully understood. In this study, we have used the human hepatoblastoma cell line (Hep G2) as an in vitro model system to delineate the effect of estradiol on multiple regulatory steps involved in hepatic HDL metabolism. Incubation of Hep G2 cells with est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 44 publications
4
10
0
1
Order By: Relevance
“…The hepatic apo A-I mRNA levels were not significantly increased at the lowest dose but displayed a clear dose-dependent relationship throughout all E2 concentrations. These findings are in agreement with previous work in vitro 38 and clearly also indicate that the variation of E2 levels within the physiological range influences plasma apo A-I and HDL cholesterol. Thus, the higher HDL cholesterol levels in female compared with male rats 7 are probably determined by their higher endogenous E2 levels.…”
supporting
confidence: 93%
“…The hepatic apo A-I mRNA levels were not significantly increased at the lowest dose but displayed a clear dose-dependent relationship throughout all E2 concentrations. These findings are in agreement with previous work in vitro 38 and clearly also indicate that the variation of E2 levels within the physiological range influences plasma apo A-I and HDL cholesterol. Thus, the higher HDL cholesterol levels in female compared with male rats 7 are probably determined by their higher endogenous E2 levels.…”
supporting
confidence: 93%
“…Our results show that the ARE site does not play a role in the modulation of apoA-I gene expression by estrogen and genistein, as indicated by a lack or response of the plasmid construct containing two ARE sites and the positive estrogenic response of plasmids not containing the ARE site (Ϫ256[⌬Ϫ148/ Ϫ42]A-I.Luc). In addition, our results showing a significant increase in apoA-I concentration in the media and in the A-I transcription activation following treatment with estradiol, while in contrast to the findings of Zhang et al (23), are clearly in agreement with previous studies (16,17,34).…”
Section: Downloaded Fromsupporting
confidence: 93%
“…We (16) and others (17) have previously shown that estrogen increases apoA-I gene transcription in liver cells in accordance with the results of clinical metabolic studies. We have also shown that genistein increases apoA-I transcription in liver cells (18).…”
supporting
confidence: 89%
“…22 Using human hepatoblastoma cells, we have shown that estradiol selectively stimulates the synthesis of LP-AI particles. 23 Although niacin is the most potent clinically used agent for elevating HDL-C and apoA-I levels in dyslipidemic patients (see review 24 ), the effect of niacin on plasma levels of LP-AI and LP-AIϩAII is not established. In the present study, using a multicenter double-blind randomized design, we have examined the effect of niacin-ER versus gemfibrozil on plasma levels of LP-AI and LP-AIϩAII particles in patients with low HDL-C.…”
Section: See Page 1707mentioning
confidence: 99%